Sosialisasi Penanganan Sampah di Dukuh Sawahan, Pendowoharjo, Sewon Bantul, Daerah Istimewa Yogyakarta - Guntur Nugroho; Muslikh Muslikh; Arini Hidayah; Ulfah Dian Indrayani; Achmad Mufid Marzuqi (Fakultas Teknik Universitas Cenderawasih, 2024)
Environmental issues are highly complex, and one of the serious problems still faced by Indonesia is waste management. Waste has negative impacts on environmental health, which in turn can affect human health. Kitchen waste, consisting of food scraps or known as organic waste, is a major concern. In a community service activity, a solution was provided through education on organic waste management and the practice of sorting and composting as a solution for household waste. The aim of this activity is to reduce the accumulation of organic waste and to increase public understanding of how to manage it. Through this program, it is hoped that residents will be able to sort, utilize, and convert kitchen organic waste into something more useful.